2017
DOI: 10.1177/0194599817691923
|View full text |Cite
|
Sign up to set email alerts
|

Elective Neck Dissection for Head and Neck Cutaneous Squamous Cell Carcinoma with Skull Base Invasion

Abstract: Objectives Skull base invasion from cutaneous squamous cell carcinoma (cSCC) via perineural spread affects survival and the rate of regional metastasis. Our objective is to investigate the factors associated with elective neck dissection (END) in this population and the survival difference with END compared with observation for patients with a cN0 neck. Study Design Case series with chart review. Setting Academic. Subjects and Methods Patients were treated surgically for head and neck cSCC with skull base inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 20 publications
2
12
0
1
Order By: Relevance
“…Elective (prophylactic) lymph node dissection is not recommended in the management of lymph nodeenegative cSCC patients, due to the low rate of nodal metastases, associated morbidity from the dissection and limited evidence in patients with mucosal head and neck SCC, a type of cancer with a significantly higher rate of nodal involvement [42,43]. A metaanalysis (17 studies) in patients with mcSCC to the parotid with no clinically evident cervical disease reported that the overall prevalence of occult disease was 22.5%.…”
Section: Surgery For Regional Nodal Diseasementioning
confidence: 99%
“…Elective (prophylactic) lymph node dissection is not recommended in the management of lymph nodeenegative cSCC patients, due to the low rate of nodal metastases, associated morbidity from the dissection and limited evidence in patients with mucosal head and neck SCC, a type of cancer with a significantly higher rate of nodal involvement [42,43]. A metaanalysis (17 studies) in patients with mcSCC to the parotid with no clinically evident cervical disease reported that the overall prevalence of occult disease was 22.5%.…”
Section: Surgery For Regional Nodal Diseasementioning
confidence: 99%
“…The indicated surgical treatment in case of nodal metastasis is therapeutic regional lymph node dissection [3,8,150]. Elective or prophylactic lymph node dissection in cases of patients affected by cSCC with negative lymph node is not recommended, given the low rate of nodal metastases, the high morbidity, and the limited evidence in patients with mucosal head and neck cSCC [154,155].…”
Section: Surgery For Regional Nodal Diseasementioning
confidence: 99%
“…11,59,60 Considering patients affected by SCC and negative lymph node, an elective or prophylactic lymph node dissection is not recommended due to the low rate of nodal metastases, the high morbidity and the limited evidence in patients with mucosal head and neck SCC. 61,62…”
Section: Surgery For Regional Nodal Diseasementioning
confidence: 99%